Abrogated transforming growth factor beta receptor II (TGFβRII) signalling in dendritic cells promotes immune reactivity of T cells resulting in enhanced atherosclerosis - Dirk Lievens; Kim L. L. Habets; Anna-Karin Robertson; Yasmina Laouar; Holger Winkels; Timo Rademakers; Linda Beckers; Erwin Wijnands; Louis Boon; Munir M. Mosaheb; Hafid Ait‐Oufella; Ziad Mallat; et al. (2012)
The importance of transforming growth factor beta (TGFβ) as an immune regulatory cytokine in atherosclerosis has been established. However, the role of TGFβ signalling in dendritic cells (DCs) and in DC-mediated T cell proliferation and differentiation in atherosclerosis is unknown. Here, we investigated the effect of disrupted TGFβ signalling in DCs on atherosclerosis by using mice carrying a transgene resulting in functional inactivation of TGFβ receptor II (TGFβRII) signalling in CD11c+ cells (Apoe−/−CD11cDNR). Apoe−/−CD11cDNR mice exhibited an over two-fold increase in the plaque area compared with Apoe−/− mice. Plaques of Apoe−/−CD11cDNR mice showed an increase in CD45+ leucocyte content, and specifically in CD3+, CD4+ and CD8+ cells, whereas macrophage content was not affected. In lymphoid organs, Apoe−/−CD11cDNR mice had equal amounts of CD11c+ cells, and CD11c+CD8+ and CD11c+CD8− subsets, but showed a subtle shift in the CD11c+CD8− population towards the more inflammatory CD11c+CD8−CD4− DC subset. In addition, the number of plasmacytoid-DCs decreased. Maturation markers such as MHCII, CD86 and CD40 on CD11chi cells did not change, but the CD11cDNR DCs produced more TNFα and IL-12. CD11c+ cells from CD11cDNR mice strongly induced T-cell proliferation and activation, resulting in increased amounts of effector T cells producing high amounts of Th1 (IFN-γ), Th2 (IL-4, IL-10), Th17 (IL-17), and Treg (IL-10) cytokines. Here, we show that loss of TGFβRII signalling in CD11c+ cells induces subtle changes in DC subsets, which provoke uncontrolled T cell activation and maturation. This results in increased atherosclerosis and an inflammatory plaque phenotype during hypercholesterolaemia.